Bioethics and Public Health: From the 1970s to the COVID-19 pandemic - Aspradaki, Aikaterini A (Bioethica, 2021)
The strong relationship between bioethics and public health has been put forward since the early 1970s. The HIV/AIDS epidemic, erupted in the 1980s, serves as a catalyst for the broadening of the bioethics frameworks by the inclusion of ethical issues faced in public health. From the beginning of the 21st century, public health ethics has been emerged as a discipline and has been established as a subfield of bioethics. Topics in public health ethics include, among others, the public health research, the ethics and infectious disease control, the ethics of health promotion and disease prevention, the ethical issues in environmental and occupational health, the public health and health system reform: allocation of resources, access, priority setting, the international collaboration for global public health, the vulnerability and marginalized populations, the public health genetics, the public health genomics. The COVID-19 pandemic seems to constitute an area of conceptual and practical overlapping of all the above-mentioned topics and gives huge boost to research interest for public health bioethics. This paper explains the relationship between bioethics and public health through two time periods and, in particular, the “early” 1970s- 1990s era and the2000s & 2010s that is the period of the emergence and establishment of public health ethics marked, at the end, by the COVID-19 pandemic.